Integrating telemedicine in assisting poison center service: Line application - Suthimon Thumtecho (2022)
Objective: To characterize Line, a mobile chat application, usage in Ramathibodi Poison Center (RPC) for further improvement of toxicological consultation services. Materials and Methods: Retrospective data were retrieved from Line messages together with concurrently recorded cases in the RPC database for six months, between November 16, 2018 and May 15, 2019. Time of consultation, time to response, types of toxins, reasons for consultation, and delivered content were recorded. Results: Over six months, 12,686 consultations were made via the hotline with 1,181 cases that used Line as an adjunct with 1,301 conversations. Median response time was three minutes. The most common poisonings were pesticides with 525 contacts (40.4%), followed by pharmaceutical agents and animal toxins. Most requests were for treatment suggestions with 731 contacts (56.2%), followed by notifying case progression and substance or animal identification. Among 1,030 files sent by consultees, the most common were photos of substances and animals for identification. Among 997 responses, most RPC staff used Line as an adjunct for treatment suggestions at 659 times (66.1%), followed by substance or animal identification and providing diagnoses. Overall, 602 protocols were delivered. Conclusion: Ten percent of all consultations were accompanied by Line usage. Most contacts were about pesticides and for appropriate treatment. RPC also used Line to effectively deliver diagnoses and treatment and increase coverage nationally.